Measuring head accelerations during heading in female soccer players using wearable sensors - Nurasyid, N.; Fellner, B.; Hermsdörfer, J. (Sportinformatik XII. 12. Symposium der dvs-Sektion "Sportinformatik und Sporttechnologie" vom 5.-7. September 2018 in Garching. Abstracts., 2018)
Soccer is responsible for the most frequent incidence of head impacts among female athletes while little is known about the absolute number and magnitude of the impacts (McCuen et al., 2015). Sport-related concussions may be associated with cognitive and vestibular deficits, but also subconcussive hits have the possibility to cause neuropsychological changes. The present study is part of a broader research project examining the cumulative effects of football heading on brain structure and function in female players from the southern German soccer league. One of our goals is to quantify and characterize the frequencyand magnitudes of headers in female soccer players over the course of two seasons, including games and practices.